A fluorescent calix[4]arene with naphthalene units at the upper rim exhibits long fluorescence emission lifetime without fluorescence quenching. Issue 19 (22nd March 2021) - Takahashi, Masaki; Tsuji, Naoya; Yazaki, Kohei; Sei, Yoshihisa; Obata, Makoto
Abstract : Macrocyclic structure brings long fluorescence lifetime emission without fluorescence quenching and TD-DFT calculations revealed π–π interactions between the naphthalene rings. Abstract : We synthesised a new compound with four naphthyl groups in the upper rims of calix[4]arene (1 ). Compared to the monomer unit, compound 1 has redshifted absorption and fluorescence, together with high fluorescence quantum yield and long fluorescence lifetime, which is extremely rare because long fluorescence lifetime emission tends to reduce the quantum yield. Single-crystal X-ray analysis and quantum calculations in the S1 state revealed π–π through-space interactions between naphthalene rings.